Effects of Covid-19 on the autonomic nervous system in elite athletes assessed by heart rate variability - Zacher, J.; Branahl, A.; Predel, H.-G.; Laborde, S. (Sport Sciences for Health, 2023)
Introduction Covid-19 is a viral airway and systemic infection which can negatively affect the function of the autonomic nervous system. Cardiovascular autonomic function is essential for peak athletic performance. The aim of this study was to assess the effects of a Covid-19 disease on the autonomic nervous system of German elite athletes using heart rate variability (HRV).